Time-dependent robustness-based condition assessment of RC bridges subjected to corrosion. (December 2021) - Wang, Siqi; Zhang, Liye; Su, Han; Du, Jinsheng
Abstract: At present, the main methods of bridge condition assessment are reliability analysis and analytic hierarchy process method. Robustness, as a measure of the structural ability to maintain the performance after the occurrence of variations, can provide a different perspective based more on the structural property itself. Although robustness has been mainly used in structural design optimization against progressive collapse and extreme events, it can also be used in assessing the condition of bridges with material deterioration. In this paper, a time-varying robustness index model is proposed to quantify the condition of the reinforced concrete bridge girder under corrosion. In this model, the robustness index represents the average performance of the concrete girder in the remaining life. The method is exemplified through a case study of an existing reinforced concrete bridge girder. Combining with the current specification, the robustness index is compared with the reliability analysis results of the girder in the case study. The result shows that when the reliability index drops below the target reliability index, the robustness index descends to Grade 5 specified in the Code for Maintenance of Highway Bridge and Culvers (JTG H11-2004) . Both results indicate that the safety of the girder cannot satisfy demand.